KONSEP KEADILAN GENDER DALAM PEMBAGIAN WARISAN (Studi Komparatif Pemikiran M. Quraish Shihab dan Munawir Sjadzali) - Ayu Faizah; Adib Adib; Ahmad Faqih Hasyim (UIN Siber Syekh Nurjati Cirebon, 2016)
The division of inheritance between men and women are often the dispute because their ratio of 2: 1, then the study was conducted with two conflicting opinions with each other, namely the interpretation of the interpretation M. Quraish Shihab al-Misbah and Munawir Sjadzali in Re-actualizing Islamic Teachings , The method used is the comparative method. Quraish explained in the commentary of al-Misbah that the division of inheritance between men and women (2: 1) is a matter that can not be changed. However, in other works Quraish allow equal division of inheritance (1: 1) in accordance with the agreement of all the heirs. While Munawir Sjadzali explicitly requires equal division of inheritance (1: 1) on the condition that women have a role. So in essence M. Quraish and Munawir have the same thought, that justice in the division of inheritance can not be seen from the property, but based on the responsibilities and roles owned.Â Keywords: justice, inheritance, Quraish, Munawir, tafsir al-Misbah